3D printing of functional biomaterials for tissue engineering. (August 2016) - Zhu, Wei; Ma, Xuanyi; Gou, Maling; Mei, Deqing; Zhang, Kang; Chen, Shaochen
Graphical abstract: Highlights: Comprehensive review of recent advances in 3D bioprinting techniques for tissue engineering. 3D bioprinting provides complex 3D biomimetic architectures for 3D cell culture. Light-assisted 3D printers emerge as new bioprinting modalities. Bioprinting vasculature network is a current focus for maintaining tissue viability. Abstract : 3D printing is emerging as a powerful tool for tissue engineering by enabling 3D cell culture within complex 3D biomimetic architectures. This review discusses the prevailing 3D printing techniques and their most recent applications in building tissue constructs. The work associated with relatively well-known inkjet and extrusion-based bioprinting is presented with the latest advances in the fields. Emphasis is put on introducing two relatively new light-assisted bioprinting techniques, including digital light processing (DLP)-based bioprinting and laser based two photon polymerization (TPP) bioprinting. 3D bioprinting of vasculature network is particularly discussed for its foremost significance in maintaining tissue viability and promoting functional maturation. Limitations to current bioprinting approaches, as well as future directions of bioprinting functional tissues are also discussed.